THE ROLE OF AI IN ENHANCING TECHNICAL VOCABULARY ACQUISITION AMONG ENGINEERING STUDENTS - Nykyporets, Svitlana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This article explores the role of artificial intelligence in supporting technical vocabulary acquisition among engineering students. Through classroom integration of AI-powered tools – such as chatbots, personalized flashcards, and writing assistants – the study demonstrates how adaptive technologies can significantly improve both vocabulary retention and practical language use in engineering contexts. The findings highlight the pedagogical benefits of AI for individualizing instruction and bridging the gap between language learning and professional communication, while also outlining future directions for research and implementation. The article also offers practical proposals for integrating AI into technical English curricula, including step-by-step implementation models, teacher training recommendations, and criteria for selecting effective AI tools. These proposals aim to guide educators and institutions in making informed decisions about using AI to enhance language instruction in engineering education.